MEŽA IZSTRĀDES PROCESU IETEKMES UZ MEŽA EKOSISTĒMU IZPĒTE UN OPTIMĀLĀS TEHNOLOĢIJAS PAMATOJUMS - Cvetkova, Ruta; Noviks, Gotfrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Intensive forest management is the resulting of destroyed natural forest structure and related loss of a number of specific habitats and species that have adapted to them. Forest machinery impact on the forests assessment is the main base for future conservation planning and management. Machinery for forestry in work process do impact on the soil, vegetation, forms the backdrop of the forest soil preparation for forest crops or natural forest regeneration. [6] Need to reduce the impact of machinery to a minimum in order to avoid the negative consequences of forest for further development and growth. Analyzed the technical impact on the forest ecosystem. It was analyzed the chemical composition of the soil before and after logging, measured ruts and summarizes the changes in the 3 years. As well measured soil density both before and after development.